PREVALENSI GANGGUAN FUNGSI KOGNITIF DAN DEPRESI PADA PASIEN STROKE DI IRINA F BLU RSUP PROF. DR. R. D. KANDOU MANADO - Hasra, Indha Wardhani P. L.; Munayang, Herdy; Kandou, Joice (e-CliniC, 2014)
Abstrak: Stroke is a clinical syndrome caused by blood circulatory disorders from one part of the brain that creates a functional disorder of the brain like neurological deficits and nerve paralysis. Depression and cognitive impairment is a results of the occurence of stroke. This study aimed to reveal the prevalence of cognitive impairment and depression in stroke patients in the neurology inpatient room F Prof. DR. R. D. Kandou Hospital Manado. This was a descriptive study with a cross-sectional design. The sample is all stroke patient in neurology inpatient room F Prof. DR. R. D. Kandou Hospital Manado who fulfilled the inclusion criteria. The results showed that 32.4 % respondents are without cognitive impairment and 67.5 % with cognitive impairment. Of the cognitive impairment group there were 27% mild cognitive impairment, 40.5% moderate cognitive impairment and there was no patient with severe cognitive impairment. The results of depression status examination showedÂ  24.3 %Â  without depression and 75.7 % with depression. Of the depression group there were 59.5% mild depression, 10.8% moderate depression, andÂ  5.4 % severe depression. The study showed that 18 participants had cognitive impairment and depression. Conclusion: From 37 respondents, there were 7 respondents (19%) had only cognitive impaiment, 10 respondents (27%) had only depression and 18 respondents (49%)Â  with cognitive impaiment and depression. Keywords: cognitive impairment, depression, stroke Â  Â  Abstrak: Stroke adalah suatu sindrom yang disebabkan oleh adanya gangguan aliran darah pada salah satu bagian otak yang menimbulkan gangguan fungsional otak berupa defisit neurologik atau kelumpuhan saraf. Depresi dan gangguan kognitif adalah salah satu akibat dari terjadinya stroke. Penelitian ini bertujuan untuk mengetahui prevalensi gangguan fungsi kognitif dan depresi pada pasien stroke di Irina F Neuro BLU RSUP Prof. DR. R. D. Kandou Manado Penelitian ini menggunakan jenis penelitian â€œobservasionalâ€ dengan desain â€œstudi cross sectionalâ€. Sampel penelitian adalah seluruh pasien stroke di Irina F Neuro BLU RSUP Prof. DR. R. D. Kandou Manado yang memenuhi kriteria inklusi. Hasil pemeriksaan fungsi kognitif didapatkan 32,4 % normal, sedangkan yang mengalami gangguan fungsi kognitif 67,5 % dimana gangguan kognitif ringan 27 %, gangguan kognitif sedang 40,5 % dan tidak ada gangguan kognitif berat. Hasil pemeriksaan status depresi didapatkan 24,3 % normal, sedangkan yang mengalami depresi 75,7 % dimana depresi ringan 59,5 %, depresi sedang 10,8 %, dan depresi berat 5,4 %. Dari hasil pemeriksaan didapatkan 18 orang dengan gangguan fungsi kognitif yang disertai dengan depresi. Kesimpulan: Dari 37 responden, didapatkan 7 orang (19%) yang hanya mengalami gangguan fungsi kognitif, 10 orang (27%) yang hanya mengalami depresi dan 18 orang (49%) dengan gangguan fungsi kognitif dan depresi. Kata kunci: gangguan fungsi kognitif, depresi, stroke